Eutrophication may compromise the resilience of the Red Sea coral Stylophora pistillata to global change. (June 2018) - Hall, Emily R.; Muller, Erinn M.; Goulet, Tamar; Bellworthy, Jessica; Ritchie, Kimberly B.; Fine, Maoz
Abstract: Environmental stressors are adversely affecting coral reef ecosystems. There is ample evidence that scleractinian coral growth and physiology may be compromised by reduced pH, and elevated temperature, and that this is exacerbated by local environmental stressors. The Gulf of Aqaba is considered a coral reef refuge from acidification and warming but coastal development and nutrient effluent may pose a local threat. This study examined the effects of select forecasted environmental changes (acidification, warming, and increased nutrients) individually and in combination on the coral holobiont Stylophora pistillata from the Gulf of Aqaba to understand how corals in a potential global climate change refugia may fare in the face of local eutrophication. The results indicate interactions between all stressors, with elevated nutrient concentrations having the broadest individual and additive impacts upon the performance of S. pistillata . These findings highlight the importance of maintaining oligotrophic conditions to secure these reefs as potential refugia. Highlights: Interactive effects of stressors are variable; coral reefs should be managed on a local scale in accordance with local data. Additive effects of nutrients and global stressors result in changes in coral symbionts leading to shifts in overall health. Gulf of Aqaba corals may be resilient to OA and warming, yet a rise in nutrients would severely impede the reef.